2005
DOI: 10.1007/s11165-005-1086-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Mentors' Views of Practical Training

Abstract: Practical knowledge and skills are necessary components of expertise. Practical training in higher education has been shown to foster students' learning and understanding of theoretical backgrounds. The attitude and skill of mentors play a central role in enhancing the quality of students' practical learning. The aims of this study were to explore mentors' experiences of the practice period and mentoring process, and to develop practical performances to improve the practice period that s included in theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…(In Sweden, prescriptionists are professionals who completed a 3-year bachelor's degree, including a 9-week professional practice experience, and have the same dispensing authority as pharmacists. 28 ) The universities do not require that the preceptors have any work experience or any particular expertise; however, they must undergo a 2-day introductory preceptor training session at a university and are asked to attend a 1-day session for further training prior to each new APPE period.…”
Section: Methodsmentioning
confidence: 99%
“…(In Sweden, prescriptionists are professionals who completed a 3-year bachelor's degree, including a 9-week professional practice experience, and have the same dispensing authority as pharmacists. 28 ) The universities do not require that the preceptors have any work experience or any particular expertise; however, they must undergo a 2-day introductory preceptor training session at a university and are asked to attend a 1-day session for further training prior to each new APPE period.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20][21] Studies showed that students found the previous curriculum fragmented and considered the theoretical studies challenging. Trends of surface-level learning also were demonstrated which was manifested in fact memorizing and difficulties knowledge application by the students.…”
Section: Evaluation Of Teaching and Learningmentioning
confidence: 99%
“…21 However, the quality of precepting in different pharmacies was reported to vary. 20 An international evaluation panel also suggested that the 6-month experiential training should be utilized in the curriculum more effectively. 18 The commitment of the entire organization has been emphasized as a prerequisite for successful education Patient and medication therapy 40 4 Medicines and society 12 5 Interaction and communication 14 6 Optional studies 18 development.…”
Section: Evaluation Of Teaching and Learningmentioning
confidence: 99%
See 2 more Smart Citations